2000
DOI: 10.1352/0895-8017(2000)105<0269:rtoiei>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Intensive Early Intervention for Children With Pervasive Developmental Disorder

Abstract: Young children with pervasive developmental disorder were randomly assigned to intensive treatment or parent training. The intensive treatment group (7 with autism, 8 with pervasive developmental disorder not otherwise specified--NOS) averaged 24.52 hours per week of individual treatment for one year, gradually reducing hours over the next 1 to 2 years. The parent training group (7 with autism, 6 with pervasive developmental disorder NOS) received 3 to 9 months of parent training. The groups appeared similar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
406
0
17

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 635 publications
(438 citation statements)
references
References 8 publications
15
406
0
17
Order By: Relevance
“…Most previous pre-post intervention studies in autism compare behavioral intervention to other philosophy based approaches as shown in Table 1 (Birnbrauer & Leach, 1993;Eikeseth et al, 2002;Howard et al, 2005;Sheinkopf & Siegel, 1998;Smith et al, 2000). These studies report behavioral intervention results in better outcomes (Schreibman, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous pre-post intervention studies in autism compare behavioral intervention to other philosophy based approaches as shown in Table 1 (Birnbrauer & Leach, 1993;Eikeseth et al, 2002;Howard et al, 2005;Sheinkopf & Siegel, 1998;Smith et al, 2000). These studies report behavioral intervention results in better outcomes (Schreibman, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies had a control group, used standardized tests and had reliable outcome measures (reviewed in Kasari, 2002). Most of the studies compared behavioral treatment programs to interventions such as ''eclectic'' programs (Eikeseth et al, 2002;Howard et al, 2005), school based intervention (Sheinkopf & Siegel, 1998), parent training (Smith, Groen, & Wynn, 2000), non-specified interventions (Birnbrauer & Leach, 1993) and no treatment (Lovaas, 1987). Most studies reported behavioral intervention to be a more effective treatment approach (Birnbrauer & Leach, 1993;Eikeseth et al, 2002;Howard et al, 2005;Lovaas, 1987;Sheinkopf & Siegel, 1998;Smith et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We are confident that EIBI based on the principles and procedures of behavior analysis works. We still have a lot of refining to do with regard to the most efficacious aspects of EIBI, and we still have not identified all of the moderators of the effects of EIBI (Herbert, Sharp, & Gaudiano, 2002;Rogers & Vismara, 2008;Smith et al, 2006), but the intervention improves the developmental trajectories of those who receive it (Campbell, 2003;Cohen, Amerine-Dickens, & Smith, 2006;Eldevik, Eikeseth, Jahr, & Smith, 2006;Helt et al, 2008;Howard, Sparkman, Cohen, Green, & Stanislaw, 2005;Lovaas, 1987;Morris, 2009, National Institute of Mental Health, 2007Odom et al, 2003;Smith, Groen, & Wynn, 2000). We know much less, however, about the acceptability of various components of EIBI to the children experiencing them (e.g., most-to-least or least-to-most prompting, amount and pace of prompting, amount of teacher directedness during instruction, types of error correction procedures, highly structured versus more naturalistic instructional conditions, types of motivational systems).…”
mentioning
confidence: 99%
“…While there was general, though not universal, opinion that a standard ''control'' treatment ought to be selected and new treatments be compared to it, there was much disagreement as to what this standard treatment ought to be. Interventions based on Applied Behavior Analysis (ABA), such as the Lovaas model (Lovaas, 1987;Smith et al, 2000a), have received the most empirical study using group designs and so might be considered the appropriate treatment for comparison. An alternative would be to use a less expensive treatment that is feasible in public school programs, such as TEACCH (Ozonoff & Cathcart, 1998;Schopler et al, 1984).…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Early social-cognitive functioning has also predicted language growth in autism (Sigman et al, 1999). Longitudinal and intervention studies have shown that individuals who are more mildly affected by autism, defined by severity of symptoms (e.g., those diagnosed with PDD-NOS versus autism) and higher intellectual level and more typical early social-cognitive functioning (Bartak & Rutter, 1973;Sheinkopf & Siegel, 1998;Smith, Groen, & Wynn, 2000b;Yirmiya & Sigman, 1991) show better outcomes.…”
Section: What Are Unique Issues In Considering the Psychosocial Treatmentioning
confidence: 99%